2005
DOI: 10.1002/maco.200503867
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a biocide effect upon microbiologically influenced corrosion of mild steel

Abstract: The microbiologically influenced corrosion (MIC) is a very dangerous process, which affects the oil industry. The activity and microorganisms' growth at the pipelines steel cause surface modifications, which can induce a more complex corrosion process. The biocide evaluation for the MIC decrease has been normally based upon microbiological tests, and just a few references mention alternating methods which can be used as criteria for their evaluation. In this work, a commercial biocide was tested, using differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The corrosion induced by C. celerecrescens seems to be low, compared to that reported for D. vietnamensis, which was isolated from the same gas pipeline [9]. However, the presence of C. celerecrescens should be considered as one of the factors affecting the corrosion processes occurring at the inner side of the gas pipeline.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The corrosion induced by C. celerecrescens seems to be low, compared to that reported for D. vietnamensis, which was isolated from the same gas pipeline [9]. However, the presence of C. celerecrescens should be considered as one of the factors affecting the corrosion processes occurring at the inner side of the gas pipeline.…”
Section: Discussionmentioning
confidence: 69%
“…This species has been identified previously in the gas pipeline, along with some SRB, such as Desulfovibrio vietnamensis and Clostridium sporogenes [9].…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated that, 50 ppm dose of glutaraldehyde suppressed sulfide production for 143 h in planktonic cells, whereas a higher dose of GA in a biofilm reactor had less effect. Hernandez et al 28) applied relatively high biocide concentration (200 ppm GA) to eliminate both of the sessile and planktonic microorganisms and decrease corrosion rates of steel.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in accordance with the LIVE/DEAD staining results ( Figure S6-1 and Figure S6-2). The loss in viability could have shifted the reaction on the biofilm/metal interface from biocatalytic to chemical (Hernández Gayosso et al 2005. The biofilm recovered to 90% of baseline activity in approximately one month after each FNA treatment.…”
Section: Reactor Performancementioning
confidence: 99%
“…The diffusional effect disappeared 12 hours after the 1st FNA treatment (Day 244.5), so the results were fitted with the circuit shown in Figure 6-5g, where the Warburg element (Wo) is replaced with a constant phase element (Qf) and a paralleled resistance (Rf). After the FNA treatments, the dead cells on the surface of the biofilm were likely sloughed from the coupon surface with vortexing, leading to a decrement in biofilm thickness, also eliminating the diffusion control effect (Hernández Gayosso et al 2005). The deviation of the double-layer capacitance from an ideal capacity (nf) was in a relatively steady state of approximately 0.82 up to Day 248, after which nf dropped gradually to 0.5094 at Day 270, indicating that the electrode surface was becoming rough and porous (Sheng et al 2007).…”
Section: Fna's Effect On Electrochemical Properties Of the Carbon Stementioning
confidence: 99%